Antibiotic Resistance Detection of Staphylococcus aureus Isolated from Dairy Cattle and Pet Animals - Yosyana, Alyaa Rifqoh Putri; Salasia, Siti Isrina Oktavia; Wasissa, Madarina; Alhadz, Ghias Ghifari; Aziz, Fatkhanuddin (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Antibiotics play a significant role in controlling bacterial infection, however, will no longer be effective because of antimicrobial resistance (AMR). Staphylococcus aureus has become resistant to various antibiotics, so detecting and analyzing genes encoding antibiotic resistance traits is important. This research aims to identify phenotypically, antibiotic sensitivity, and detect antibiotic-resistant genes in S. aureus isolated from dairy cattle and pet animals. Samples from dairy farms in Boyolali total of 30 samples and 62 samples of pet animals in Yogyakarta and Semarang were used. Phenotypic and genotypic identification results based on 23S rRNA and nuc genes showed 80% (24/30) dairy milk samples and 19,35% (12/62) pet animal samples were S. aureus positive. Based on antibiotic susceptibility test, dairy milk S. aureus isolates are resistant to penicillin G (50%), oxacillin (25%), tetracycline (21%), ampicillin (17%), gentamicin, cefoxitin, and amoxicillin (13%), clindamycin (4%), and still sensitive to erythromycin (100%). Pet animal S. aureus isolates showed resistance to oxacillin and erythromycin (13,3%), tetracycline, penicillin G, and clindamycin (6,67%), but still sensitive to gentamicin, ampicillin, cefoxitin, and ciprofloxacin and amoxicillin (100%). These results showed S. aureus dairy milk and pet animal isolates phenotypically have resistance almost 50% to various antibiotics but are still sensitive to erythromycin. The result of this research indicated there are majority of multidrug-resistant S. aureus strains in dairy milk and pet animals threaten public health. These results can be used as a basic strategy for controlling and preventing multidrug resistance in S. aureus.